Proceedings of the 52nd ACM Conference on Computers and People Research 2014
DOI: 10.1145/2599990.2600014
|View full text |Cite
|
Sign up to set email alerts
|

Using professional consultants to mentor CIS students on a simulated consulting project

Abstract: Students who graduate from the Computer Information Systems major at James Madison University tend to be hired by consulting firms. In support of this, our program has developed an IT Consulting class. This class is team taught by members of the consulting firms that hire our students and a faculty member. The consulting firms also serve as mentors to the students in the class as student teams respond to a simulated Request for Proposal. This paper describes our class and the mentoring role taken by the consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Few studies from the skills development literature (Aasheim, Li, & Williams, 2009;Dillon & Lending, 2014;Trauth, Farwell, & Lee, 1993) and turnaway research offer important insights into career interventions, initial employment and IT career persistence. Dillon and Lending (2014) found that 70% of college IT students who are mentored by seasoned IT professionals find employment at graduation. Trauth et al (1993) argue that mentorship and internship programs presumably bridge the IT skills gap that exists between academic training and the dynamic IT industry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies from the skills development literature (Aasheim, Li, & Williams, 2009;Dillon & Lending, 2014;Trauth, Farwell, & Lee, 1993) and turnaway research offer important insights into career interventions, initial employment and IT career persistence. Dillon and Lending (2014) found that 70% of college IT students who are mentored by seasoned IT professionals find employment at graduation. Trauth et al (1993) argue that mentorship and internship programs presumably bridge the IT skills gap that exists between academic training and the dynamic IT industry.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the IT skills development literature (Aasheim et al, 2009;Dillon & Lending, 2014;Trauth et al, 1993) provide evidence and reasons for the favorable outcomes of career interventions. However, the studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation